Analisis Penerapan Akuntansi Keperilakuan Sumber Daya Manusia Pada Usaha Mikro Kecil dan Menengah di Kelurahan Kota Baru, Kecamatan Alok Timur, Kabupaten Sikka - Kristiana Daputri; Yosefina Andia Dekrita; Fransiscus De Romario (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to determine the behavior that arises from MSME actors regarding the existence of accounting science and its application, this is because there are still many MSMEs who do not understand what accounting is and what accounting is like. This research was conducted in Kota Baru Subdistrict by examining several MSME actors in Kota Baru Subdistrict who are members of it. Researchers use a qualitative approach with the type of research, namely descriptive. Qualitative research is research that produces written or verbal data from a person or observed behavior, and the technique for collecting the data is using observation, interviews and documentation. The results of this research show that the behavior given by MSME actors in response to the existence of accounting knowledge and its application in the business world results in MSME actors already knowing the existence of accounting science, but there are still MSMEs who do not understand what accounting is.